Resistivity Imaging of Mataloko Geothermal Field By Mise-Á-La-Masse Method - Enjang Jaenal Mustopa; Wahyu Srigutomo; Doddy Sutarno (Institut Teknologi Bandung, 2011)
Mise-á-la-masse (MAM) measurement has been carried out in the Mataloko geothermal field, Flores, East Nusa Tenggara. The survey was conducted along 16 survey lines in a radial configuration to collect 176 sounding sites. The purpose of the measurement is to image a promising reservoir zone and to correlate the results with the previous geosciences surveys for locating the best drilling target. Three-dimensional (3D) inversion scheme was applied to interpret MAM data. The subsurface resistivity structure obtained from 3D inversion result shows that a low resistivity (1 − 10 ohm.m) structure is widely distributed in the southwest and northeast of the well MT-3/MT-5 at the depth 0 − 100 m. On the other hand, in the deeper part of the survey area, it is recognized that a resistivity in the western part is lower than in the eastern part of the area. The fluid flow tests of well MT-5 produced dry saturated steams of 19.3, 12.6 and 17.4 ton/h at wellhead pressures of 4.0, 6.0, and 5.0 kscg, respectively. Furthermore, the fluid has high enthalpies whose values are 2746, 2755, 2763, 2768, and 2771 kJ/kg at wellhead pressure of 4.0, 5.0, 6.0, 7.0, and 7.5 kscg, respectively. The incorporation of MAM data analyses results with the geosciences data makes it possible to recommend the location of the best target for the drilling site.